National aggregates and individual disaffiliation: An international study - Pablo Bra\~nas-Garza; Teresa García-Mu\~noz; Shoshana Neuman (Bar-Ilan University, Department of Economics, 2009)
Using a dataset of 15,000 subjects from 32 western countries, the current study examines individuals who were raised in a certain religion and at some stage of their lives left it. Currently, they define their religious affiliation as 'no religion'. A battery of explanatory variables (country-specific, personal attributes and marriage variables) was employed to test for determinants of this decision. It was found that the tendency of individuals to leave their religion is strongly correlated with the degree of religious diversity of their country and with their spouse's religious characteristics. Moreover, personal socio-demographic features seem to be less relevant.
Keywords: Z12; J12; J13; D13; 330; religion; national aggregates; disaffiliation